ISTIDRAJ IN THE QUR'AN IN THE TAFSIR MAFATIH AL-GHAIB BY FAKHR AL-DIN AL-RAZI - Ramdhan, Tri Wahyudi (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2023)
This study aims to find out the interpretation of al-Razi about the verses of istidraj and the analysis of the interpretation of al-Razi about the verses of istidraj in the tafsir of Mafatih al-Ghaib. Knowledge about istidraj is very important so that we as Muslims do not fall into istidraj behavior and can avoid things that lead to these behaviors. The method of uncovering it all is a library where the author uses data and data sources in the form of documents both from journals and books. The result of this study where Razi grouped into 5 verses about Istidraj First, Surah al-A'raf verse 182 indicates that Istidraj leads to destruction, second Surah al-Qalam verse 44 indicates the cause of being struck by istidraj, third Surah Ali-'Imran verse 178 explains istidraj for the disbelievers, fourth Surah al-An'am verse 44 explains about torture after pleasure and fifth Surah al-Mu'minun verses 55-56 explain Wealth and children do not always mean goodness.